2018
DOI: 10.1002/pd.5350
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis: First‐trimester maternal serum free β‐hCG and the risk of significant copy number variants

Abstract: Low first-trimester serum β-hCG is associated with an increased risk of significant CNVs on CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(67 reference statements)
1
2
1
Order By: Relevance
“…Contrary, the relationship between serum PAPP-A levels with CNVs is still unclear. Although large population-based studies have reported an association with low PAPP-A levels, neither Bornstein et al [18] nor our study have identified a significant association. This difference could be due to an effect of the sample size of the included cohort or the defined PAPP-A cutoff point.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary, the relationship between serum PAPP-A levels with CNVs is still unclear. Although large population-based studies have reported an association with low PAPP-A levels, neither Bornstein et al [18] nor our study have identified a significant association. This difference could be due to an effect of the sample size of the included cohort or the defined PAPP-A cutoff point.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
“…Indeed, the residual risk of a clinically significant CNV is 3 times higher when low β-hCG levels are detected or 2 times higher when fetal NT ≥3.5 mm is detected in high-risk pregnancies (cFTS ≥1/250) (Table 2). A similar association has been previously reported by Bornstein et al [18]. Contrary, the relationship between serum PAPP-A levels with CNVs is still unclear.…”
Section: Discussion/conclusionsupporting
confidence: 87%
See 1 more Smart Citation
“…Maternal serum screening has been used for prenatal screening of foetal aneuploidies since the 1950s 27 . Recent evidence has shown that abnormal serum screening results are associated with foetal pCNVs 28 . In our study, although the detection rates of aneuploidies in pregnancies with an increased maternal serum screening risk were not significantly increased, the detection rates of pCNVs and lpCNVs in these pregnancies elevated significantly.…”
Section: Discussionmentioning
confidence: 99%